Peningkatan Hasil Belajar Siswa Melalui Pendekatan TaRL pada Mata Pelajaran Pendidikan Pancasila di SMAN 1 Rantau Selatan - Patricia Sinurat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to improve student learning outcomes in Pancasila Education subjects through the application of the Teaching at the Right Level (TaRL) approach in class X-1 of SMA Negeri 1 Rantau Selatan. The background of this study is the low learning outcomes of students caused by differences in learning abilities that have not been accommodated in the learning process. TaRL is an approach that adjusts learning to the level of ability of each student, not only based on class level. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles, each consisting of the planning, action, observation, and reflection stages. Learning begins with a diagnostic assessment to determine students' initial abilities, which then become the basis for dividing study groups. The results of the study showed a significant increase in learning outcomes, indicated by an increase in the average score from 73 in the pre-cycle to 89 in the second cycle. In addition, student activity and involvement in the learning process also increased. These findings indicate that the TaRL approach is able to answer students' learning needs more specifically and has a positive impact on the learning process and outcomes. This approach is recommended as an alternative strategy in differentiated learning.